THE CURATIVE METHODS OF MAS (Motile Aeromonas Septicaemia) USE LEAF MANGROVE EXTRACT (Rhizophora sp) ON JAMBAL SIAM FISH (Pangasius hypophthalmus) - Mastuti, Rini; Syawal, Henni; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
ABSTRACTThe research was conducted in May until August 2017 in Parasites and Fish Disease Laboratory of Marine and Fisheries Faculty University of Riau,and also in the Integrated Chemical Laboratory of Mathematics and Natural Science of Health Faculty Riau Muhammadiyah University. The purpose of the study was todetermine the ability of Rhizophoraspto cure the disease which is caused by MAS (Motile Aeromonas Septicaemia) and showed from the profile of Siamese Shark (Pangasius hypophthalmus)erythrocyte. The method was an experimental method with a Completely Randomized Design (CRD), one factor with four treatments, there were : control without curing, 1300 ppm, 1600 ppm, and 1900 ppmrespectively. The immersions was applied twice in two days by leaf mangrove extract (Rhizophora s)p for about 5 minutes. The result showed that leaf  mangrove extract (Rhizophora sp) able to cure Siamese Shark from MAS (Motile Aeromonas Septicaemia) by the immersions method. The best dose was at 1600 ppm wich was shown by the total erythrocyte was 290 x 104 cell/mm3, haemoglobin level was 9,30 g/dL, haematocrit value was 29,66 %, and the survival rate was 84,61%.Keywords: Rhizophora sp, Motile Aeromonas Septicaemia, Haematology